2020
DOI: 10.1186/s13012-020-01047-2
|View full text |Cite
|
Sign up to set email alerts
|

Costing the implementation of public health interventions in resource-limited settings: a conceptual framework

Abstract: Background Failing to account for the resources required to successfully implement public health interventions can lead to an underestimation of costs and budget impact, optimistic cost-effectiveness estimates, and ultimately a disconnect between published evidence and public health decision-making. Methods We developed a conceptual framework for assessing implementation costs. We illustrate the use of this framework with case studies involving interventions for tuberculosis and HIV/AIDS in resource-limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 17 publications
2
68
0
Order By: Relevance
“…Understanding these start-up and implementation costs is key for public health decision making, yet very few economic analyses have accounted for these costs, and even then have not actually measured these costs prospectively. 24 Similar to other studies that considered cost allocation of prevention efforts, we found that personnel were the major driver of cost in all countries during programme strengthening. 25,26 We also found that the costs for initial evaluation, start-up, and initial training accounted for the great majority of costs, and the ongoing running costs for the LTBI programme were much lower.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Understanding these start-up and implementation costs is key for public health decision making, yet very few economic analyses have accounted for these costs, and even then have not actually measured these costs prospectively. 24 Similar to other studies that considered cost allocation of prevention efforts, we found that personnel were the major driver of cost in all countries during programme strengthening. 25,26 We also found that the costs for initial evaluation, start-up, and initial training accounted for the great majority of costs, and the ongoing running costs for the LTBI programme were much lower.…”
Section: Discussionsupporting
confidence: 87%
“…*The number of household contacts that are estimated to be eligible for tuberculosis preventive treatment include all children younger than 5 years, and household contacts older than 5 years who are expected to test positive with the tuberculin skin test based on prevalence data collected at sites 16 and published data 17 (average for Canada 0•55, average for all other countries 0•70). phase showed ongoing improvement at sites, compared with the initial cascade analysis (appendix pp [19][20][21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 93%
“…We conducted a cost-effectiveness analysis (including implementation strategy costs [ 22 ];) based on program costs for personnel, supervision, training, and materials across both active study arms. Personnel costs included those for counselors, nurses, and expert clients, who over the course of the study were asked to recall how much time they spent weekly delivering intervention activities.…”
Section: Methodsmentioning
confidence: 99%
“…Planning for Implementation, Scaling Up, and Sustaining Impact While calls to explicitly account for the costs attributable to implementation strategies are not novel [51], reporting remains uncommon [23]. Proposals of pragmatic approaches are still recent [52,53], particularly when considering preimplementation activities that may have a direct impact on scale of implementation [54] or program feasibility and sustainability [55]. In estimating costs for implementing combinations of EBIs in HIV/AIDS for six US cities, we derived public health department costs attributable to planning activities to coordinate implementation in local healthcare facilities [9].…”
Section: Scale Of Implementation: Intended Populations and Service Dementioning
confidence: 99%
“…There are a number of high-quality microcosting examples in both the public health [66] and the implementation science literature [54]. Similarly, some studies have proposed approaches for the standardized reporting of preimplementation and implementation component costs [52,54,55,67] but these have not yet been used widely or applied to population-level EBIs. Moreover, CEA typically uses assumptions of constant average costs (i.e., linear cost functions) yet the functional form of costs can matter, particularly for widespread implementation of EBIs [68].…”
Section: Costs Of Implementation Componentsmentioning
confidence: 99%